Numerical transient analysis of random leakage in time and frequency domains. Issue 1 (2nd January 2016) - Ferrante, Marco; Capponi, Caterina; Collins, Richard; Edwards, Jonathan; Brunone, Bruno; Meniconi, Silvia
ABSTRACT: Models of water pipeline systems should take into account the distribution in space and time of user demands and leakage. In the usual approach such a distribution is simplified lumping the system outflows at a reduced number of nodes. To investigate the effects of such a simplification, in this paper we explore by numerical models, both in the time and in the frequency domain, the uncertainty introduced by the random variation in leak size, location and number. The novelty is also in considering the number of leaks as a parameter. In the time domain, results show that the damping increases with the number of leaks. The spreading of the simulated pressure signals increases with time whereas it decreases with the number of leaks. In the frequency domain, the local minima and maxima values of the impedance are affected by the number of leaks for a given total outflow from the system.